CALVING PATTERN IN KANKREJ CATTLE AND MEHSANA BUFFALO AT AN ORGANIZED FARM IN NORTH GUJARAT - PATEL, MP; PAREEK, NK; ANKUYA, KJ; RATHOD, BS; PRAJAPATI, KB (The Indian Journal of Animal Reproduction, 2016)
The seasonality in calving pattern at an organized farm in North Gujarat was recorded to present statistics on regional trends for calving pattern. For assessing the seasonality of calving patterns, the data on 821 Kankrej cattle and 486 Mehsana buffalo (calving between 2006 and 2015) maintained at Livestock Research Station, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Gujarat was considered. The month and season had impact (p
Keywords: Calving Index; Calving pattern; Kankrej cattle; Mehsana buffalo; Seasonality